Role of Clinical Palpation in Evaluation of Cervical Lymph Node in Oral Squamous Cell Carcinoma - SM Anwar Sadat; Sufia Nasrin Rita; Shoma Banik; Md Nazmul Hasan Khandker; Md Mahfuz Hossain; Md AI Khan (Update Dental College, 2013)
A cross sectional study of 29 cases of oral squamous cell carcinoma with or without  cervical lymph node metastasis was done among Bangladeshi patients from January 2006 to December 2007. Majority of the study subjects (34.5%) belonged to the age group of 40-49 years. 58.6% of the study subjects were male, while remaining 41.4% of them were female. 51.7% of the lesions were located in the alveolar ridge where the other common sites were buccal mucosa (27.6%) and retro molar area (13.8%). Half of the study subjects (51.7%) were habituated to betel quid chewing followed by 37.9% and 10.3% were habituated to smoking and betel quid-smoking respectively. Grade I lesions was most prevalent (75.9%) in the study subjects.  Majority of cases presented with Stage IV lesions (55.2%). The sensitivity, specificity, positive predictive value, negative predictive value & accuracy of clinical palpation method for determining metastatic cervical lymph nodes were 93.33%, 64.29%, 73.68%, 90% and 79.3% respectively. Careful and repeated clinical palpation plays important role in evaluation of cervical lymph nodes though several modern techniques may help additionally in the management of oral cancer. DOI: http://dx.doi.org/10.3329/updcj.v1i2.13978 Update Dent. Coll. j. 2011: 1(2): 02-06